Notas para una historia de la ciencia ficción en España - Moreno Serrano, Fernando Ángel (Dicenda. Estudios de lengua y literatura españolas, 2008)
Because of the constant oblivion in studies and handbooks, is necessary an analysis of the Spanish science fiction literature. So, we should be aware that the principles that determine his mechanisms, structures and characteristics are very different than the realist literature. Neither the usual signs of fantastic literature show all his estetic possibilities, then make a wrong impression. In that situation, it doesn’t help his too popular origin or the paperback editions, who only capture the most superficial and simple of the sciencie fiction atmosphere. Only a few exceptions (but very good) viewed the poetic possibilities of the genre. Afortunatly, since the seventies, publishers and writers have been improved techniques, topics and atittudes until now.